Intelligent Production System Planning with Virtual Design Reviews. (2016) - Koechling, D.; Berssenbruegge, J.; Schluessler, J.; Stoecklein, J.
Abstract: The conventional way of visualizing the material flow in a production system is to use simulation tools and their integrated symbols and pictograms. By going this way, a good relation to reality does not really exist and thus it is nearly impossible to provide for all contingencies. This paper introduces a procedure which enables a virtual design review of the planned process layout in the HD visualization center at the Heinz Nixdorf Institute. This means that production planners have the opportunity to do a virtual inspection of the production including the visualized material flow. As a result, the planning certainty and the system comprehension of all parties involved significantly increase, so that the presented procedure serves as a valuable decision support. This paper describes the steps to be taken from production-data to an optimized material flow verified in a virtual inspection.